Advanced understanding of genetic risk and metabolite signatures in construction workers via cytogenetics and metabolomics analysis. (November 2019) - Raja, Ganesan; Jang, Yoon-Kwan; Suh, Jung-Soo; Prabhakaran, Vasantha-Srinivasan; Kim, Tae-Jin
Graphical abstract: Highlights: Finding the genetic risk and metabolic signature in daily construction workers. Our understanding of metabolism is evolving the clinical biomarker metabolites. An energy and several amino acid pathways can be affected and impacted. Abstract: Clinical biomarkers of building construction workers (BCW)-related genetic risk and metabolome fluctuations are still lacking, and profiling and validating them is challenging. Metabolomics is well suited to address this need, and serum is a valuable and accessible biofluid. This study aimed to characterize the 1 H nuclear magnetic resonance (NMR)-based serum metabolomics and discrimination of patients with different clinical features of BCW (n = 30) and, healthy control (HC: n = 30). Karyotypes and chemical profiling were analyzed in all 60 subjects. The deproteinized serum samples was discriminated using orthogonal projections to latent structures discriminant analysis (OPLS-DA). With good quality metaphases, we performed in situ karyotyping techniques in blood cells, and identified Trisomy 21 (47, XY, +21), reciprocal translocation (45, XY, der (15;21)), and 7q11 microdeletion syndrome. Target profiling and quantification was performed for around 50 metabolites. With metabolic profiling technology, the chemical reaction between metabolites was measured. Moreover, a cytokinesis block micronucleus cytome assay considerable significant differences between micronuclei, nucleoplasmic bridges, and apoptotic and necrotic cell frequency with healthy voluntaries. Diversified chromosomal aberrations and chromatid breaks were observed in the BCW. The present investigation could contribute substantially to genetic risk and metabolites, with regard to the genotoxic effects in construction workers exposed to various genotoxic compounds.